Teaching business ethics: Questioning the assumptions, seeking new directions - Furman, Frida Kerner (Journal of business ethics, 1990)
An examination of leading textbooks suggests the predominance of a principle-based model in the teaching of business ethics. The model assumes that by teaching students the rudiments of ethical reasoning and ethical theory, we can hope to create rational, independent, autonomous managers who will apply such theory to the many quandary situations of the corporate world. This paper challenges these assumptions by asking the following questions: 1. Is the acquisition of principle-based ethical theory unproblematic? 2. What is the transferability of classroom learning to the business context? 3. Is it appropriate to consider complementary models in the teaching of business ethics? The last question is approached from the perspective of virtues-based ethics, from the insights of feminist ethics, and from a culturally grounded orientation to moral values and norms.